STRATEGI GREEN HUMAN RESOURCE MANAGEMENT DALAM PROGRAM MAKAN BERGIZI GRATIS DI LEMBAGA PENDIDIKAN MILITER: PENDEKATAN BERKELANJUTAN UNTUK KESEJAHTERAAN PERSONEL - Aspani, Rony; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
The Indonesian government’s Free Nutritious Meal (MBG) program aims to improve nutritional status, health, and learning capacity of students across educational institutions, including military academies. This study examines the implementation of Green Human Resource Management (GHRM) in supporting MBG at the Army Military Science Development Education Center (Pusdikpengmilum TNI AD). Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis of policy and operational procedures. Findings reveal that GHRM practices—such as green recruitment, green training, and environmentally based performance rewards—enhance MBG quality, strengthen environmental awareness culture, and positively impact institutional reputation. Integrating sustainability principles into HRM promotes optimization of local food supply chains, energy efficiency, and effective kitchen waste management. This study contributes theoretically to GHRM literature and offers practical implications for national nutrition policy within military institutions